Effect of turmeric and garlic supplementation to fermented Sauropus androgynus-bay leaves containing diet on fat deposition and broiler meat composition - Santoso, U.; Fenita, Y.; Kususiyah, K.; Agustian, A. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This study aimed to examine the effect of turmeric and garlic inclusion to fermented Sauropus androgynus-bay leaves (FSBL) containing diet on fat deposition, and chemical composition of broiler meats. Two hundred 15-day-old female broilers were distributed into 5 treatment groups with 4 replications as follows. Control feeds with commercial feed additive (T0); Feeds with 1.25% FSBL (T1); Feed with FSBL plus 1 g turmeric (T2); Feed with FSBL plus 2 g garlic (T3); Feed with FSBL plus 1 g of turmeric and 2 g garlic (T4). It was shown that the fat deposition in the abdomen was significantly affected (P<0.01). Furthermore, the inclusion of turmeric and garlic to FSBL containing diet did not affect fat, protein, moisture and ash contents, but increased arginine, methionine and histidine (P<0.01). The addition of turmeric and/or garlic to the FSBL containing diet significantly influenced lauric acid, myristic acid, linolenic acid, cis-11-eicosenoic acid, cis-4,7,10,13,16,19-docosahexaenoic acid (P<0.05), n-3 fatty acid and n-6/n-3 fatty acid ratio (P<0.01). In conclusion, turmeric plus garlic supplementation improved amino acid profiles and changed fatty acid profiles. The possible interaction should be considered when we formulated feed additive from medicinal plant mixtures